2015
DOI: 10.1371/journal.pone.0119814
|View full text |Cite
|
Sign up to set email alerts
|

Use of Smokeless Tobacco by Indian Women Aged 18–40 Years during Pregnancy and Reproductive Years

Abstract: ObjectivesThis paper discusses patterns of daily smokeless tobacco (SLT) use and correlates of poly SLT use among married women aged 18–40 years in a Mumbai slum community with implications for tobacco control.MethodsUsing a mixed methods approach, the study included a structured survey with 409 daily SLT users and in-depth interviews with 42 women. Participants for the survey were selected using a systematic sampling procedure (one woman in every fourth eligible household). Univariate and bivariate analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 39 publications
5
52
0
Order By: Relevance
“…SLT use is found to be positively associated with its use by partner or peers 23 24 . In a study conducted among married women at Mumbai, India, SLT use was found to be attributed for reducing stress, providing pleasure, associated companionship with peers at workplace and in the neighbourhood, increasing energy for workload and suppressing hunger when dietary requirements were not met 25 . Further, SLT use is often initiated at an early age as children and youth are often exposed to it when involved in purchase activities for their mothers and other older family members 26 .…”
Section: Determinants Of Slt Usementioning
confidence: 99%
“…SLT use is found to be positively associated with its use by partner or peers 23 24 . In a study conducted among married women at Mumbai, India, SLT use was found to be attributed for reducing stress, providing pleasure, associated companionship with peers at workplace and in the neighbourhood, increasing energy for workload and suppressing hunger when dietary requirements were not met 25 . Further, SLT use is often initiated at an early age as children and youth are often exposed to it when involved in purchase activities for their mothers and other older family members 26 .…”
Section: Determinants Of Slt Usementioning
confidence: 99%
“…Oral smokeless tobacco products are placed in the mouth, cheek or lip and sucked (dipped) or chewed [1] . India is one of the largest producers and consumers of tobacco, most of it in the smokeless tobacco form and available in different brands across the country [2] . It is estimated that 5500 adolescents consume tobacco every day in India and every year 4 million young people are starting the consumption of tobacco regularly [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Use of SLT is also believed to be helpful during the early period of pregnancy by reducing vomiting and increasing the appetite. 41 …”
Section: Discussionmentioning
confidence: 99%